Gray Matter Changes in Subjects at High Risk for Developing Psychosis and First-Episode Schizophrenia: A Voxel-Based Structural MRI Study - Nakamura, Kazue; Takahashi, Tsutomu; Nemoto, Kiyotaka; Furuichi, Atsushi; Nishiyama, Shimako; Nakamura, Yumiko; Ikeda, Eiji; Kido, Mikio; Noguchi, Kyo; Seto, Hikaru; Suzuki, Michio (Frontiers in Psychiatry, 2013)
Objectives: The aim of the present study was to use a voxel-based MRI method to investigate the neuroanatomical characteristics in subjects at high risk of developing psychosis compared with those of healthy controls and first-episode schizophrenia patients. Methods: This study included 14 subjects with at-risk mental state (ARMS), 34 patients with first-episode schizophrenia, and 51 healthy controls. We used voxel-based morphometry (VBM) with the Diffeomorphic Anatomical Registration Through Exponentiated Lie Algebra (DARTEL) tools to investigate the whole-brain difference in gray matter volume among the three groups. Results: Compared with the healthy controls, the schizophrenia patients showed significant gray matter reduction in the left anterior cingulate gyrus. There was no significant difference in the gray matter volume between the ARMS and other groups. Conclusion: The present study suggests that alteration of the anterior cingulate gyrus may be associated with development of frank psychosis. Further studies with a larger ARMS subjects would be required to examine the potential role of neuroimaging methods in the prediction of future transition into psychosis.